Major air pollution and climate policies in NYC and trends in NYC air quality 1998–2021 - Lau, Kathleen; Guo, Jia; Miao, Yuqi; Ross, Zev; Riley, Kylie W.; Wang, Shuang; Herbstman, Julie; Perera, Frederica (Frontiers in Public Health, 2024)
Introduction Air pollution poses serious health risks to humans, with particular harm to children. Objectives To address the gap in understanding the efficacy of policies to reduce exposure to air pollution, we sought to assess the temporal relationship between the enactment of major air pollution and climate policies in NYC and trends in air quality during the period 1998–2021. We used previously available data from citywide monitoring and new data from the Columbia Center for Children’s Environmental Health (CCCEH) longitudinal cohort studies of mothers and children living in communities in Northern Manhattan and the South Bronx. Methods We utilized publicly available citywide air monitoring data for particulate matter (PM2.5) and nitrogen dioxide (NO2) from 2009 to 2021 from the New York City Community Air Survey (NYCCAS) database and CCCEH cohort data on residential exposure to PM2.5 and NO2 and personal exposure to polycyclic aromatic hydrocarbons (PAH) during pregnancies occurring from 1998–2016 and 1998–2021, respectively. We compared annual and overall reductions in PM2.5 and NO2 citywide and reductions in PAH concentrations in the cohort studies. Results As previously reported, annual average concentrations of pollutants in NYC dropped significantly over time. Between 1998 and 2021, PM2.5 and NO2 concentrations were reduced citywide by 37 and 31%, respectively. In our CCCEH cohorts, between 1998 and 2016, the annual average PM2.5 and NO2 concentrations also decreased significantly by 51 and 48%, respectively. Between 1998 and 2020, PAH concentrations decreased significantly by 66%. Discussion/conclusion While it is not possible to link improved air quality to a single policy, our analysis provides evidence of a cumulative beneficial effect of clean air and climate policies enacted between 1998 and 2021 both city-wide and in our cohorts residing in communities that have been disproportionately affected by air pollution. There are important implications for health benefits, particularly for children, who are known to be especially vulnerable to these exposures. The results support further environmental and social policy changes to prevent the serious health impacts of air pollution from fossil fuel emissions.